2023
DOI: 10.1038/s41586-022-05592-2
|View full text |Cite
|
Sign up to set email alerts
|

Vertical organic electrochemical transistors for complementary circuits

Abstract: Organic electrochemical transistors (OECTs) and OECT-based circuitry offer great potential in bioelectronics, wearable electronics and artificial neuromorphic electronics because of their exceptionally low driving voltages (<1 V), low power consumption (<1 µW), high transconductances (>10 mS) and biocompatibility1–5. However, the successful realization of critical complementary logic OECTs is currently limited by temporal and/or operational instability, slow redox processes and/or switching, incompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
160
0
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(171 citation statements)
references
References 61 publications
7
160
0
4
Order By: Relevance
“…By varying the lateral geometrical dimensions of the device, the authors demonstrated ultra-high transconductance in the range of hundreds of mS for the larger geometries. A similar approach has also been exploited by both Italian and non-Italian research groups for the fabrication of vOECT-based n-type organic transistors and complementary circuits [ 84 , 85 ]. Moreover, researchers from FBK recently reviewed the impact of planar and vertical geometries on OFET performances for flexible electronics [ 86 ].…”
Section: Transistor-based Sensorsmentioning
confidence: 99%
“…By varying the lateral geometrical dimensions of the device, the authors demonstrated ultra-high transconductance in the range of hundreds of mS for the larger geometries. A similar approach has also been exploited by both Italian and non-Italian research groups for the fabrication of vOECT-based n-type organic transistors and complementary circuits [ 84 , 85 ]. Moreover, researchers from FBK recently reviewed the impact of planar and vertical geometries on OFET performances for flexible electronics [ 86 ].…”
Section: Transistor-based Sensorsmentioning
confidence: 99%
“…[1][2][3] In principle, OECTs operate upon the effective volumetric ion injection from the electrolyte into the polymeric channel to modulate the bulk conductivity of channel. [4][5][6] The identifying characteristic of typical poly(ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) OECTs is that the alternation in hole density occurs over the entire PEDOT:PSS channel, [7,8] enabling efficacious ionic-to-electronic transduction with a high transconductance (g m = ΔI DS / ΔV G ), [9] which is especially desirable as it is necessary for scenario applications demanding high sensitivity, [10], for example, in vivo recordings of brain activity and electrocardiograms. [11] Generally, the external input gate bias (V G ) is applied to regulate g m to be maximized, the prolonged application of which is disadvantageous to reduced power consumption and vulnerable biological system.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for relatively younger organic transistors when compared to their traditional inorganic counterparts. Organic transistors have gained attention as a promising technology for the development of low-cost, flexible, and large-area electronic devices. A subgroup of organic transistors, the organic electrochemical transistor (OECT), has emerged with particularly suitable characteristics for bioelectronic applications such as biosensors and biopotential recordings. OECTs are advantageous in bio-interfacing applications due to the mixed ionic/electronic conduction of their channel materials. This mixed conduction is ideal for ion-to-electron transduction, allowing for highly attainable amplification compared to inorganic or organic field effect transistors, providing quality biopotential recordings and good acquisition of small biosensor signals. Although applications such as these have benefited from OECT-related progress, further advances are needed to enable stable devices, high-density arrays, and complementary logic. …”
Section: Introductionmentioning
confidence: 99%